The Role of Ethics in Language Teaching - Barrantes Montero, Luis Guillermo (2012)
Se propone el fundamento de la dimensión ética en la enseñanza de lenguas. Se señalan las divergencias en el ethos de las culturas moderna y post-moderna para contextualizar el tema. A partir de ello se resalta la condición de persona como valor máximo a cuya promoción integral han de orientarse las diversas acciones humanas. Dado que la enseñanza de lenguas implica una confrontación entre mismidad y la otredad, resulta imperioso recuperar su identidad como disciplina humanística –más allá del instrumentalismo positivista propio de la expansión del capitalismo económico financiero– con el fin de cimentar la valorabilidad ética de las acciones que se toman en ella. An attempt is made to provide a basis for the ethical dimension of language teaching. Discrepancies about ethos in modern and post-modern cultures are discussed to contextualize the topic. That will be the starting point to give the person as such the highest value, toward which all integral development of human actions must be oriented. Since language teaching implies a confrontation between sameness and otherness, it is crucial to recover its identity as a humanistic discipline–beyond the positivistic instrumentalism characteristic of current financial economic capitalism–with the aim of establishing the ethical value of any actions taken within its scope.